2007
DOI: 10.1192/bjp.bp.107.036673
|View full text |Cite
|
Sign up to set email alerts
|

Insight, psychopathology and global functioning in schizophrenia in urban Malawi

Abstract: Insight, psychopathology and functioning are related in schizophrenia, but it is unclear whether insight relates independently to functioning after controlling for psychopathology. Equally, any such relationship may vary culturally. We investigated the relationship between insight, psychopathology and functioning in 60 patients with schizophrenia in Mzuzu, a town in Malawi. After controlling for psychopathology, functioning was associated with the ;symptom relabelling' dimension of insight (P=0.01). This preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
4
10
0
1
Order By: Relevance
“…More specifically, consistent with an extant literature [7,22,[24][25][26] insight was positively correlated with the overall level of functioning and severity of psychopathology as measured by the global functioning scale (GAF). In the light of other studies that have reported an inverse relationship between severity of psychopathology and level of insight [8,21,30,53], such discrepancies could be explained by the inconsistency found in the operational definition of insight [36] and functional outcomes (i.e., studies may explore general level of functioning or more specific aspects, e.g., occupational and social functioning), compounded by small or heterogeneous sample characteristics (e.g., current clinical state) and clinical scales used amongst studies [18,23].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…More specifically, consistent with an extant literature [7,22,[24][25][26] insight was positively correlated with the overall level of functioning and severity of psychopathology as measured by the global functioning scale (GAF). In the light of other studies that have reported an inverse relationship between severity of psychopathology and level of insight [8,21,30,53], such discrepancies could be explained by the inconsistency found in the operational definition of insight [36] and functional outcomes (i.e., studies may explore general level of functioning or more specific aspects, e.g., occupational and social functioning), compounded by small or heterogeneous sample characteristics (e.g., current clinical state) and clinical scales used amongst studies [18,23].…”
Section: Discussionsupporting
confidence: 74%
“…However, despite the proliferation of work in this area, the nature of the relationship between insight and neurocognitive impairment, severity of psychopathology or functional recovery still remains unclear [19][20][21][22][23]. On cross-sectional analyses, lack of insight has been closely linked to poor global functioning [24][25][26], and poor treatment compliance [27,28].…”
Section: Introductionmentioning
confidence: 96%
“…For instance, a multicentre study conducted among 524 patients with schizophrenia on oral and long acting olanzapine using a different instrument reported that majority of their subjects had impairment with a fifth of them having good level of functioning [25]. Other studies have reported similar range of figures among people with schizophrenia with regards to functioning using the same instrument [36], or with the use of different instrument [37]. Generally, recent findings suggest a relatively better level of functioning in a large proportion of individuals with schizophrenia when compared to the traditional Kraepelin classification [26], and the difference is possibly due to advancement in treatment.…”
Section: Psychopathology and Impairment With Associated Factorsmentioning
confidence: 65%
“…Previous research works on schizophrenia have indicated strong linkage between increasing frequency of symptoms with poorer level of functioning. Arguably, there is established relationship between functioning and lower severity of schizophrenic symptoms, greater levels of productive activity and higher scores on other health-related QOL measures [37]. Similarly, positive correlation between reduced psychopathology and increasing GAF score i.e.…”
Section: Psychopathology and Impairment With Associated Factorsmentioning
confidence: 99%
“…Während dieses Vorgehen bei Patienten mit guter Krankheits-und Behandlungseinsicht geradezu eingefordert wird und sie sich zusätzlich Spezialwissen aus dem Internet herunterladen (Crumlish et al 2007;Freyberger u. Schneider 2011), lehnen Patienten mit der gegenteiligen Krankheitseinstellung die kooperative Zusammenarbeit mit den professionellen Helfern oftmals kategorisch ab. Um mit diesen Patienten über ein verbessertes Wissen in einen konstruktiven Dialog treten zu können, zählen neben einer intensiven Beziehungsarbeit insbesondere psychoedukative Gruppen im stationären Bereich mittlerweile zum Behandlungsstandard (American Psychiatric Association 2006;Bäuml 2008;Deutsche Gesellschaft für Psychiatrie, Psychotherapie und Nervenheilkunde 2006).…”
Section: Mangelnde Krankheits-und Behandlungseinsichtunclassified